1998
DOI: 10.1103/physrevlett.81.49
|View full text |Cite
|
Sign up to set email alerts
|

Charge Asymmetry in Hadroproduction of Heavy Quarks

Abstract: A sizeable difference in the differential production cross section of top and antitop quarks, respectively, is predicted for hadronically produced heavy quarks. It is of order αs and arises from the interference between charge odd and even amplitudes respectively. For the TEVATRON it amounts up to 15% for the differential distribution in suitable chosen kinematical regions. The resulting integrated forward-backward asymmetry of 4-5% could be measured in the next round of experiments. At the LHC the asymmetry c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
375
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(394 citation statements)
references
References 9 publications
18
375
1
Order By: Relevance
“…The SM prediction is dominated by O(α 3 S ) QCD interference effects and is 5% in the lab frame [46,47,48,49]. There is a discrepancy of about 2σ between theory and experiment.…”
Section: Top Pair Productionmentioning
confidence: 97%
“…The SM prediction is dominated by O(α 3 S ) QCD interference effects and is 5% in the lab frame [46,47,48,49]. There is a discrepancy of about 2σ between theory and experiment.…”
Section: Top Pair Productionmentioning
confidence: 97%
“…Within QCD it was shown that [3] higher order correction can give an asymmetry of 5%. If the data is real, then the contribution from new physics is of order 15%.…”
Section: W ′ In This Workmentioning
confidence: 99%
“…If the asymmetry is true, it will indicate the presence of new physics, because within the SM the asymmetry is only up to about 5% [3]. So far, a few explanations [4,5,6] have been put forward to account for such a large asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…One is thus forced to rely on the subdominant qq and qg initial states, making use of the strong correlation between the rapidity of the tt system and the direction of the incoming quark. Event-by-event, a positive forward-backward asymmetry in qq(qg) → tt + X translates into a positive charge asymmetry in the forward regions |y| > y 0 [5,6]. This forward-central charge asymmetry is (assuming CP conservation) a natural LHC observable.…”
Section: Introductionmentioning
confidence: 99%